Character Values in Baris Arug Dance: Sasak Local Wisdom and Pedagogical Potential for Elementary Education - Sukarni, Sri; Salim, Agus; Yustika, Tesa; Tarenaksa, Babat Nufus; Yusoh, Ruslan (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2026)
This study documents Baris Arug, a traditional Sasak dance from Longserang Village, Lingsar District, West Lombok Regency, and examines the character values embedded in its historical background, performance structure, symbolic elements, and sociocultural functions. It also explores the dance’s pedagogical potential for elementary education. Using a qualitative descriptive design, data were collected from October to December 2024 through observations of rehearsals and community performances, semi-structured interviews with 17 purposively selected informants—one dance elder and leader, four senior dancers, four musicians, three community leaders, and five younger members—and document analysis. The data were analyzed iteratively through data reduction, data display, and conclusion drawing and verification. The findings show that community oral histories associate Baris Arug with the collective joy of farmers after successfully cultivating new agricultural land. Performed by thirteen male dancers in a commander-led formation, the dance embodies togetherness, courage, discipline, hard work, leadership, responsibility, and gratitude through marching movements, costumes, masks, farming tools, music, and ritual offerings. Baris Arug also functions as community entertainment, a means of strengthening social cohesion and cultural identity, and a medium for transmitting local values across generations. These findings indicate that Baris Arug offers culturally grounded material for local-content and extracurricular learning in elementary schools. However, because the study did not examine classroom implementation, its educational contribution should be understood as a pedagogical potential that requires further development and empirical evaluation.